Status of the Elephants in Kuldiha Sanctuary, Orissa - Swain, D. (Indian Forester, 1996)
Elephant census was carried out by the author twice in the Kuldiha Sanctuary of Orissa, one in June and the other in December, 1992. The result of such census has been discussed in this papcr. The Elephants in this sanctuary live in highly fragmented groups due to scarcity of food and biotic interference. Suggestions have been made to save this fragmented population from annihilation.